Ethical Considerations for Echinoderms: New Initiatives in Welfare - Crespi Abril, Augusto Cesar (2023)
This paper explores the ethical considerations surrounding research on echinoderms, a group of invertebrates that has recently garnered attention in the scientific community. The importance of responsible animal handling and the need for an ethical framework that encompasses echinoderms are emphasized. The 3Rs principle, advocating for the replacement of conscious living vertebrates with non-sentient material in research, is discussed as a guiding tool in current animal research practices. As invertebrates are generally classified as non-sentient animals, the replacement dimension tends to favor them as prevalent models in experimental research. While it currently lacks the means to assess the mental states of invertebrates, there is undeniable evidence of social behavior in many species, suggesting that a lack of interactions with these organisms could potentially adversely affect their wellbeing. In the last few years, considerable progress has been made in developing an ethical framework that takes invertebrates into account, particularly cephalopods, crustaceans, and echinoderms. In this context, we discuss the development of a broader conceptual framework of 5Rs that includes responsibility and respect, which may guide practices ensuring welfare in echinoderms, even in the absence of any particular normative.